Valuation, leverage and the cost of capital in the case of depreciable assets: Revisited - Diderik Lund (Copenhagen Business School (CBS), Department of Economics, 2006)
Levy and Arditti (1973) introduced depreciable assets into the Modigliani and Miller (1958) model, and analyzed the implications for the cost of capital. Assuming that the firm reinvests indefinitely to maintain a constant expected cash flow, they found that depreciation increases the cost of capital before and after tax. Most of their assumptions are maintained. However, commitment to perpetual reinvestment is in most cases not a reasonable assumption. Without it, depreciation decreases the cost of capital before and after tax. The effect of depreciation is less in absolute value than in Levy and Arditti, but not insignificant.
hdl:10398/7583
Keywords: G31; H25; 330; Cost of capital; depreciation; corporate taxes